The materiality key: how work on empirical data can improve analytical models and theoretical frameworks for multimodal discourse analysis - Maiorani, Arianna (Frontiers in Communication, 2024)
This article is a critical reflection on the way the notion of materiality informed the project and the development of the The Kinesemiotic Body project carried out by a UK and German research teams and of the model of analysis it adopted, the Functional Grammar of Dance. It starts with an excursus of some of the most interesting developments in other discipline that turned to the investigation of materiality as an epistemological perspective, and it shows how the same type of focus has impacted on multimodal discourse analysis focusing on movement-based communication. The overarching theme that characterises this multidisciplinary attention to materiality is its anchoring function to the temporal and spatial coordinates in which social phenomena are contextualised, which is taken as the fundamental condition for shaping our perception and understanding of the world in all areas of experience and knowledge. A more specific example of how the notion of materiality impacted on the development of movement-based discourse analysis will be provided by an example of analysis of rich movement data captured live from professional dancers from the English National Ballet. considered through different approaches (Multimodal Discourse Analysis, Engineering, Computer Science, etc.) makes the examples of empirical data analysis proposed here particularly appropriate to the consideration of the notion of materiality as an interdisciplinary one and provides a clear connection with John Bateman's discussion of materiality in relation to the development of Multimodality as a practice that encompasses borders between disciplines and research areas (Bateman et al. 2017, Bateman 2019,2022). This article will also show how the consideration of the materiality of dance allowed in primis for the further development of the Functional Grammar of Dance (Maiorani 2021, Maiorani et al. 2022, Maiorani and Liu 2023), which is now a more comprehensive and even more flexible tool that scholars have started to use for analysing movement-based communication in dance performances other than ballet or even outside the domain of dance altogether (see